2018
DOI: 10.1136/emermed-2018-207588
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of pre-hospital diagnostic accuracy studies

Abstract: CRD42016039306.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…Similar to findings in the review by Wilson et al 38 , this study found higher specificity than sensitivity, i.e. prehospital clinicians were better at excluding HVS than they were at recognising HVS.…”
Section: Limitationssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to findings in the review by Wilson et al 38 , this study found higher specificity than sensitivity, i.e. prehospital clinicians were better at excluding HVS than they were at recognising HVS.…”
Section: Limitationssupporting
confidence: 88%
“…The sensitivity 88% (95% CI 82-92%) and specificity 99% (95% CI 99-99%) of pre-hospital clinicians' diagnosis of HVS were slightly higher than the pooled estimate obtained in a metaanalysis on pre-hospital diagnostic accuracy by Wilson et al 38 . This means that pre-hospital clinicians were better at correctly identifying patients with HVS and without HVS on average than conditions studied in other pre-hospital diagnostic accuracy studies.…”
Section: Limitationscontrasting
confidence: 58%
“…EMS providers rely on their personal skills and the automated machine annotations in their interpretation of the PH-ECG. However, previous studies have shown that EMS providers tend to have lower sensitivity (0.63 to 0.95) and specificity (0.72 to 0.94), 9 and automated ECG interpretation algorithms tend to have lower sensitivity. 10 Although systematic over-reading of PH-ECGs by a medical command physician could overcome these shortcomings, 11 it has not been widely implemented by EMS systems because of excessive cost and the lack of around-the-clock access to specialized physicians.…”
mentioning
confidence: 90%
“…Most modern emergency systems are based on paramedics. They are considered sufficiently sensitive and specific in identifying patients with life threatening conditions, but there is a notable heterogeneity between studies and a wide range of estimates [14]. In the past, all ambulances in Poland used to have a physician on board.…”
Section: Discussionmentioning
confidence: 99%